Enhancing Dynamic Capabilities through the Implementation of the Electronic Corruption Prevention Program (E-Proksi) in Kendari City - Sartono, Sartono; Alam, Syamsul; Yusuf, Muhammad; Taufik, Taufik; Afdal, Andi Ahmad Malikul; Laxmi, Laxmi (Universitas Dharma Wacana, 2024)
This study aims to explore the role of information technology innovation, particularly E-Government, in enhancing governance dynamics and efficiency in addressing challenges related to corruption. Employing a qualitative approach with phenomenology, the research focuses on elucidating individual experiences with the implementation of E-Proksi at the Kendari City Inspectorate. Data collection involved interviews and observations, with data validation conducted through triangulation to ensure accuracy and consistency. The findings indicate that the technological innovation introduced by the E-Proksi application in Kendari City has positively influenced both corruption prevention and the enhancement of public services. However, the application encounters challenges such as public preference for traditional methods, insufficient socialization, and suboptimal political and regulatory support. Adaptive organizational culture and dynamic capabilities emerge as crucial factors in ensuring the program's success. Continued efforts to increase public participation and responsiveness to change are essential for achieving governance that is efficient, transparent, and accountable. Through ongoing strategic updates and attentive consideration of community feedback, E-Proksi is anticipated to significantly contribute to fostering a more effective, cleaner, and adaptable government in Kendari City.